ROS-Responsive PLGA-NPs for Co-Delivery of DTX and DHA for Colon Cancer Treatment - Roberta Cassano; Sonia Trombino; Federica Curcio; Roberta Sole; Gabriella Calviello; Simona Serini (International Journal of Translational Medicine, 2024)
The aim of this work was to evaluate the antineoplastic effect of newly synthesized nanoparticles based on poly(lactic-co-glycolic acid) (PLGA) alone or PLGA esterified with 2,2′-[propane-2,2-diylbis (thio)] diacetic acid (TKL), loaded with docetaxel (DTX) and/or docosahexaenoic acid (DHA), as innovative site-specific therapeutic carriers. The obtained materials were characterized by FT-IR and 1H-NMR, while the dimensional analysis of the nanoparticles obtained was performed by Dynamic Light Scattering. The encapsulation efficiency of the nanoparticles was evaluated, and in vitro skin permeation tests were also performed. The antitumor activity of the nanomaterial was studied in the human adenocarcinoma HCT116 cell line. In particular, viability tests in bidimensional culture, as well as in tumor spheroids, were conducted. The use of these nanocarriers could facilitate the stable and efficient delivery of DTX and DHA through the upper segments of the gastrointestinal tract to the colon. In addition, the presence of the ROS-sensitive 2,2′-[propane-2,2-diylbis (thio)] diacetic acid in their matrix should promote the site-specific release of DTX in the tumor mass, where high levels of reactive oxygen species could be found.